Museum & Institution for Cartoon & Comic Art (MICCA) - Jahangir Arko, Chowdhury Asif (BRAC University, 2012)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture in Architecture, 2012.